INOVASI LAYANAN KEPENDUDUKAN DISPENDUKCAPIL MELALUI PROGRAM JEMPUT BOLA TERPADU DI KABUPATEN SIDOARJO - Heru Irianto; Susi Ratnawati; Jusmitha Hartin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2022)
Rapid technological developments encourage the government as a public organization to innovate services to the community. This is intended to increase the reach of ownership of population documents to the community. This research is a qualitative descriptive study, and the location of this research was conducted at the Population and Civil Registration Office of Sidoarjo Regency. Based on the results of this study, it can be seen that the focus of the research which consists of relative advantages can be said to have succeeded in increasing the scope of ownership of population documents. Compliance can be said to have succeeded in increasing the scope of ownership of resident documents. Complexity can be said to have succeeded in increasing the scope of document ownership. tried can be said to have succeeded in increasing the scope of document ownership. Ease can be said to have succeeded in increasing the scope of document ownership. The supporting factors of this integrated pick-up program include human resources (HR), leadership capital, and organizational structure capital. However, on the other hand there are also obstacles in this program, namely cultural or organizational barriers and administrative pressures and barriers.